HAZARD SEISMIC STUDIES FOR THE ROMANIAN CAPITAL - APPLING THE SHAKE MAP METHOD - Balan S.F.; Cioflan C.O.; Apostol B.F. (My University, 2006)
The shake map methodology for seismic hazard studies has been applied to a sector of Bucharest, the capital of Romania. Geological and geotechnical profiles are known for this region. We have chosen as seismic input the event of 30 August 1986, MW = 7.1. We discuss the propagation of a synthetic signal with known source characteristics, from source to bedrock and back to surface. It is possible to produce surface synthetic signals in the studied area, having very similar characteristics (accelerations) to the observed ones. © 2006 Akadémiai Kiadó, Budapest.
Keywords: ACCELERATION; BEDROCK; SEISMIC HAZARD; SHAKE MAP